The cobalt content effect on the electrochemical behavior of nickel hydroxide electrodes - Ortiz, Mariela Gisela (2012)
In this paper, the study of nickel hydroxide porous electrodes containing different concentrations of cobalt as additive (2-10%), polytetrafluoroethylene (PTFE) as binder material and prepared by chemical impregnation on nickel sintered substrate, are presented. The characterization of the different electrodes is performed using optical techniques such as scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX) and electrochemical techniques as cyclic voltammetry, charge-discharge curves and electrochemical impedance spectroscopy (EIS). The results indicate that the concentration of 5% metallic Co improves the electrochemical behavior of the active material.